THE INFLUENCE OF SIMRS IMPLEMENTATION AND WORK MOTIVATION ON WORK PRODUCTIVITY MEDIATED BY EMPLOYEE PERFORMANCE AT PULANG PISAU REGIONAL GENERAL HOSPITAL, CENTRAL KALIMANTAN - Ruriyansi; Farida Yuliaty; Taufan Nugroho; Kosasih; Vip Paramarta; Fitriana (RADJA PUBLIKA, 2025)
Hospital Management Information System (SIMRS) and to reinforce work motivation in order to enhance organizational productivity through employee performance at Pulang Pisau General Hospital. The primary objective is to examine the influence of SIMRS implementation and work motivation on work productivity, with employee performance serving as a mediating variable. Employing a descriptive and verificative method with a quantitative approach, data were collected through questionnaires and observations, and subsequently analyzed using path analysis. The results indicate that SIMRS implementation, work motivation, employee performance, and work productivity are generally categorized as satisfactory. Both individually and collectively, SIMRS implementation and work motivation exert a positive and significant effect on employee performance. Furthermore, employee performance demonstrates a positive and significant influence on work productivity. SIMRS implementation exerts a direct, positive, and significant effect on productivity, while the direct effect of work motivation on productivity, although positive, is statistically insignificant. However, both SIMRS implementation and work motivation exert significant indirect effects on productivity through employee performance. Overall, the findings underscore that enhancing work productivity within hospital organizations is highly contingent upon the effectiveness of well-managed information systems, the consistency of work motivation, and the professionalism of employee performance. The integration of these three factors establishes a conducive work environment that supports organizational achievement and advances the quality of healthcare services.